# math

8(x+2)-4x +7 I need help!

multiply the parenthsis

8x + 16-4x +7
then combine the x terms, and combine the number terms.

the answer to this problem is 4x+23

1. 👍 0
2. 👎 0
3. 👁 111

## Similar Questions

1. ### Math

The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out how to do this right so I left off the >0 and tried to solve the equation. x+20 evaluates to x+20 x-12 evaluates to x-12 Multiplying x+20 by x-12 is a classic

asked by Sabrina on September 24, 2010
2. ### Maths

you have to solve the following by finding the value of x and y. can u help please? x+3(x+1)=2x 1+3(x-1)=4 2x-2(x+1)=5x 2(3x-1)=3(x-1) 4(y-1)+3(y+2)=5(y-4) 3y+7+3(y-1)=2(2y+6) These are exercises in standard algebraic manipulation

asked by number 420 on April 22, 2007
3. ### math 117

5/(x+6)+ 2/(x^2+7x+6)= 3/(x+1) Rewrite x^2 +7x +1 as (x+6)(x+1) Multiply both sides of the equation by that expression. You get 5(x+1) + 2 = 3(x+6) Multiply out the parentheses and combine similar terms. You will be left with a

asked by Diana on July 11, 2007
4. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

asked by Abby on September 17, 2015
5. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

asked by Abby on September 18, 2015
6. ### math

multiply and combine like terms 5(3x-2y) - (x+6y)

asked by Loe on October 5, 2011
7. ### to bobpursley,math,correction

(sqrt3 + 5)(sqrt3 -3) ? multiply that out sqrt3*sqrt3 -3sqrt3 +5sqrt3 -15 now combine and simplify terms. yes the problems is: ((sqrt3)+5)((sqrt3)-3) if i put in my calculator what the squareroot of 3 it will give me 1.7 so if i

asked by Jasmine20 on January 26, 2007
8. ### maths algebra

3a-2(2a+4) 3a-2(2a + 4) you multiply the parenthesis by -2, giving you 3a -4a -8 combine like terms -a-8

asked by nicky on October 31, 2006
9. ### college algebra

i need some help with this pleez! f(x+6) f(x)=3x^2-5x+3 if u could explain in steps that would be great! :) If f(x) = 3x^2-5x+3, then f(x+6) = 3(x+6)^2 + 5(x+6) + 3 Multiply that out and combine terms.

asked by Val on March 14, 2007
10. ### Math

Do 3x²y and x² combine to make 4x²y? I original multiplied 3x² by y because of order of operations, and now the next step is to combine like terms. Does it combine? I am in Math 1 class.

asked by Help Like terrms on November 9, 2019

More Similar Questions